Why cycling matters for Smart Cities. Internet of Bicycles for Intelligent Transport. (October 2016) - Behrendt, Frauke
Abstract: This article develops the concept of "smart velomobility" that is concerned with networked practices, systems and technologies of cycling. The concept draws on velomobility, Smart Mobility/Intelligent Transport Systems (ITS), Smart Cities and the Internet of Things (IoT). The article presents results from an empirical study, where 80 riders of a networked fleet of e-bikes discuss their experience of smart velomobility. The results show how digital and physical mobilities merge, the way riders of the networked fleet interact with the data, how they share the data and how they feel tracked (privacy). The conclusion sketches out future research of "smart velomobilities" and also points out the policy and innovation potential of cycling as active, sustainable and networked mode of transport in the context of Smart Cities and the Internet of Things. Abstract : Graphical abstract Highlights: Develops the concept of smart velomobility. Draws on velomobility, Intelligent Transport, Smart Cities, Internet of Things (IoT). Presents results from an empirical study with a networked bike fleet. Experience of smart velomobility: datafication of cycling, privacy, rewards. Innovation potential of active, sustainable and smart/intelligent mode of transport.